Oxidative stress in occupational exposure to styrene vapors and dangerous chemicals in the shipbuilding industry - Pigini, Daniela; Paci, Enrico; Guglielmetti, Rachele; Tranfo, Giovanna; Spagnoli, Mariangela; Fetoni, Annarita; Tricarico, Laura; Sisto, Renata (Frontiers in Toxicology, 2023)
Introduction: In the shipbuilding industry, workers are exposed to a variety of dangerous chemicals, styrene being one of them. The International Agency for Research on Cancer classified styrene as a chemical belonging to group 2A, which means it is probably carcinogenic to humans. This study aimed at evaluating the oxidative stress effects due to occupational exposure to styrene and other chemicals. Materials and methods: Styrene urinary metabolites, such as mandelic acid and phenylglyoxylic acid, and the urinary biomarkers of oxidative stress, i.e., oxidation products of DNA and RNA and of proteins, were measured in a group of 17 workers and compared to the concentrations found in a group of 17 healthy volunteers who had not been exposed to chemicals. Results and discussion: Statistically significant differences were found for 8-oxo-7,8-dihydroguanine (8-oxoGua) and 8-oxo-7,8-dihydro-2′-deoxiguanosine (8-oxodGuo) concentrations that are higher in workers than in the control group. The workers performing the tasks of painting are the most exposed to styrene and show higher concentrations of 8-oxo-7,8-dihydroguanosine (8-oxoGuo). Workers performing the tasks of wood refining and welding are less exposed to styrene but have higher concentrations of 8-oxoGua and 8-oxodGuo. Conclusion: The exposure scenario in shipbuilding is a complex one, in which different xenobiotics are simultaneously present. The oxidative stress effect biomarkers, obtained from the oxidation product of RNA and DNA, are promising, sensitive, but not specific.